2014
DOI: 10.1093/neuonc/nou217
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the SMO oncogene by miR-326 inhibits glioma biological behaviors and stemness

Abstract: This work suggests a possible molecular mechanism of the miR- 326/SMO axis, which can be a potential alternative therapeutic pathway for gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 50 publications
(22 reference statements)
1
59
0
2
Order By: Relevance
“…Several miR-326 targets, including Bcl-2 (38) in osteosarcoma, FSCN1 (39) and NOB1 (41) in gastric cancer, SMO (47) and PKM2 (43) in glioma and CCND1 (25), phox2a (44), SP1 (45) and ADAM17 (46) in lung cancer, have been identified. In the present study, KRAS was validated as a novel target of miR-326.…”
Section: Discussionmentioning
confidence: 99%
“…Several miR-326 targets, including Bcl-2 (38) in osteosarcoma, FSCN1 (39) and NOB1 (41) in gastric cancer, SMO (47) and PKM2 (43) in glioma and CCND1 (25), phox2a (44), SP1 (45) and ADAM17 (46) in lung cancer, have been identified. In the present study, KRAS was validated as a novel target of miR-326.…”
Section: Discussionmentioning
confidence: 99%
“…Было показано, что экспрессия SMO обратно коррелирует с экспрессией miR-326, являясь её прямой мишенью. Более того, гиперэкспрессия miR-326 снижала пролиферативную активность и стволовые свойства культуры ОСК глиомы U251 [20]. При этом miR-326 способна ингибировать сигнальный путь PI3К (phosphatidylinositol 3-kinase) в клетках глиобластомы [21].…”
Section: Smo Gli1 Ptchunclassified
“…Введение miR-326 может являться новой стратегией терапии [35]. miR-326 ингибируется PI3-киназным каскадом [21] [ [20][21][22], [35], [37] miR-675-5p, ген которой находится внутри гена длинной некодирующей РНК Н19, играет роль в развитии ответа на гипоксию и гипоксия-опосредованном ангиогенезе [81] [81], [82] короткая длина зрелых микро-РНК ограничивает дизайн проб [101]. Несомненным преимуществом RNA-seq является возможность глубокого анализа дифференциальной экспрессии, в том числе поиска вариаций (SNP и др.…”
Section: (рис 2)unclassified
“…For this reason, miRNAs or corresponding synthetic RNA sequences are being explored as potential drugs against a variety of human disorders [124]. A qRT-PCR and western blot study at Harbin Medical University demonstrated that Smo was highly expressed in multiple glioma cell lines and this over-expression correlated with poor survival [125]. A previous study demonstrated that miR-326 serves as a negative regulator of the Hh pathway by targeting Gli2 and Smo [126].…”
Section: Biologics As Hedgehog Pathway Inhibitorsmentioning
confidence: 99%